Konfigurasi Makna Postingan Duta Wisata Uda Uni Kota Padang Pada Akun @Adwindopadang Dalam Membangun Citra Diri - maisya, salsa ratu; Sary, Marisa Puspita; Sutjipto, Vera Wijayanti; Safitri, Dini; Putri, K. Y.S.; Romli, Nada Arina (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Social media, particularly Instagram, is used for communication and sharing activities through photos and videos. Additionally, this platform serves to shape self-image and respond to various commnets. For example is @adwindopadang, a group of youth touris ambassadors (Uda Uni Kota Padang) who act as stakeholders in the tourism sector. This research aims to analyze how @adwindopadang builds their self-image through Instagram. The study employs Ferdinand de Saussure’s semiotic theory to understand the meaning construction from the photos and texts posted by the @adwindopadang Instagram. It uses a constructivist paradigm with a qualitative descriptive approach. The data examined includes the photos and descriptions on the account. The research findings indicate that @adwindopadang construct self-image through a combination of verbal and non-verbal messages, reflected in the captions, photography, style, distinctive fashion choices. The conclusion drawn is that the self-image built by @adwindopadang displays characteristics of simplicity, intelligence, humility, modernity, fasion-forwardness, and inspiration, successfully creating a positive image on social media